Political religions in the Greco-Roman world : discourses, practices and images - Koulakiotis, Elias (Cambridge Scholars Publishing, 2019)
Until the 1980s, historical treatments of ancient religion focused mainly on myth, cult and ritual as a way to interpret the mental structures or primary emotions of ancient peoples, but, in the last few decades, a "political turn" in the study of religion has taken hold. This volume serves to diversify our understanding of the political conceptualizations and implementations of religious practice in the ancient Mediterranean region from the 7th Century BCE to the 4th Century CE, in both Greek and Roman contexts. The underlying question taken up here is: in what situations was Greco-Roman religious practice articulated, communicated, and perceived in political contexts, both real and imagined? Written by experts in the fields of archaeology, linguistics, art history, historiography, political science and religion, the chapters of this volume engage the plurality and the diversity of the Greco-Roman religious experience as it receives and negotiates power relations